Fossil wood of Duabanga from the Siwaliks of Sindhuli area, eastern Nepal (Journal of Nepal Geological Society, 1997)
A fossil wood belonging to the extant genus Duabanga Buch-Ham of Sonneratiaceae has been represented the collection from the Siwaliks of the Sindhuli district, eastern Nepal. As the modem equivalents of the fossil wood grow now in the Indo-Malayan region, its presence in the Siwaliks of Nepal is phytogeographically important and indicates more humid climate at the time of deposition.